NAEYC'S position on developmentally appropriate practice a panel discussion and critique [videorecording]. (National Association for the Education of Young Children, 1987)
The panel -- Barbara Bowman, Patty Calvert, Constance Kamii, Lilian Katz, and David Weikart--debates one of the most important topics in early childhood education today. Held at the NAEYC Conference in Washington, D.C. in November 1986.